INSTRUCTIONAL LEADERSHIP OF THE PRINCIPAL IN THE TRANSFORMATION OF VISION AND MANAGEMENT OF ACHIEVEMENT-BASED LEARNING: A CASE STUDY OF SDN 1 BUGEL - Retno Susilowati; ngurah ayu nyoman murniati; Supandi (SOSIOEDUKASI, 2026)
This research is motivated by the challenge of school visions, which are often trapped in administrative slogans without a real internalization of the work culture. This study aims to analyze the role of instructional leadership, vision transformation, and achievement-based learning management at SDN 1 Bugel. Using a qualitative case study method, data was collected through interviews, observations, and document review. The results indicate that the principal successfully transformed into an instructional leader through dialogic clinical supervision and ongoing mentoring. The school vision was systemically internalized through assertive communication strategies and strategic budget support. An evaluation of learning management demonstrated a positive transition toward an outcomes-based model and the utilization of educational report card data, despite ongoing administrative constraints. In conclusion, the success of the achievement ecosystem is determined by "lived leadership" and adaptive governance synergy.